THE EFFECTS OF 12-WEEK JUDO TRAINING ON ANAEROBIC, AEROBIC FITNESS AND BODY COMPOSITION OF JUNIOR BLIND ATHLETES - NGHIA, LY DAI; MUONGMEE, PRATOOM (Journal of Exercise and Sport Science, 2009)
Judo for the blind has been developed rapidly and international competition continues to gain popularity. In Vietnam, Judo for the blind took shape and developed in Ho Chi Minh City (2004). Although there were some researches focused on rehabilitation, growth and development of physical and metal disability individuals, there was few research on blind athletes. The aims of this study were to find the changes in anaerobic fitness, aerobic fitness and body composition of junior blind athletes after 12-week judo training. Purposive sampling included 20 junior blind athletes who were Vietnamese national junior team members (10 males and 10 females with age ranging from 14 - 19 years) In this group, 15 persons were classified to be in B1 category while the rest were in B2 category. The instruments used in this study included Monark 828 Ergometer (for Wingate and Astrand-Ryhming Tests) to measure anaerobic peak power, relative peak power, anaerobic capacity and VO2max, and Inbody 720 Body Composition Analyzer, Biospace Co. Ltd. to measure intracellular fluid, extracellular fluid, protein mass, mineral mass, fat mass, percent body fat, weight, height and BMI. The data was analyzed by using SPSS software, paired samples t-test. Significant level was set at 0.05. The results of the study were concluded as follows: 1. After 12-week Judo training, the anaerobic peak power of both male and female athletes increase significantly (male: 458.82±70.80W v.s. 442.28±94.58W, female: 364.32±37.47W v.s. 334.78±70.84W). The relative peak power of male and female athletes increase significantly (male: 8.38±1.62W/kg v.s. 7.94±1.99W/kg, female: 6.97±0.65W/kg v.s. 6.35±1.16W/kg). The anaerobic capacity of junior blind athletes also increase significantly (male: 381.73±48.27W v.s. 362.68±51.24W, female: 282.51±37.56W v.s. 265.93±40.58W). There was not a statistical significant difference of female athletes’ anaerobic fatigue between pre-test and post-test. However, anaerobic fatigue of male junior blind athletes increase significantly (45.14±10.58% v.s. 39.76±12.88%). 2. There was no significant difference in relative VO2max between pre-test and post-test in both male and female athletes. 3. After 12-week judo training, the follow indexes of male athletes were significantly higher than before training, that are intracellular fluid (24.85±1.64l v.s. 22.83±2.18l), protein mass (10.64±1.98kg v.s. 9.46±0.40kg), weight (58.62±6.12kg v.s. 56.40±5.60kg) and BMI (22.62±1.86 v.s. 21.76±1.63). The follow indexes of male athletes were significantly lower than before training, that are fat mass (9.15±1.36kg v.s. 10.09±1.82kg) and percent body fat (15.60±1.90% v.s. 17.70±2.16%). While there was no significant difference of extracellular fluid, mineral mass and height between pre-test and post-test. In female athlete group, the follow indexes were significantly higher than before training, that are intracellular fluid (20.01±1.48l v.s. 18.32±1.77l) and protein mass (8.01±0.67kg v.s. 7.55±0.75kg). While fat mass (12.07±1.40kg v.s. 13.24±1.87kg) and percent body fat (23.10±2.77% v.s. 25.20±2.97%) were significantly lower than before training. There was no significant difference of extracellular fluid, mineral mass, weight, height and BMI between pre-test and post-test. The final conclusion is that the 12-week judo training program has affected the Vietnamse national blind junior judo athletes by increasing anaerobic fitness and decreasing percent body fat significantly. However, an affected by no change in relation VO2max values was observed.